(untitled) (The Batuk, 2024)
Marital adjustment is a crucial aspect of family life, profoundly influenced by individuals’ mental health and past experiences. This study examines the relationship between childhood maltreatment, personality development, and adult marital adjustment. A sample of 385 individuals aged 25 to 40 participated, with data collected through convenience sampling. Utilizing tools such as the Big Five-Personality Inventory (BFI-10), JVQ-R2, Screener Sum Version, Adult Retrospective Form, and Marital Adjustment Test (MAT), the study sought to replicate previous findings regarding the impact of adverse childhood experiences on adult mental health. Results indicate a significant association between childhood maltreatment and adult mental health, with implications for marital adjustment. Specifically, individuals reporting childhood maltreatment exhibited greater difficulties in marital adjustment. Furthermore, personality traits were found to be shaped by childhood experiences, with notable correlations observed. Neuroticism demonstrated a negative correlation with marital adjustment, whereas extraversion, openness, and loyalty exhibited positive associations. These findings underscore the complex interplay between early-life experiences, personality development, and adult relationship functioning. Understanding these dynamics can inform interventions aimed at promoting healthy marital adjustment and mitigating the adverse effects of childhood maltreatment on adult mental health.